The female social role in the exhibition: “The Daily Life of Women in Other Times” (Cadernos de Sociomuseologia, 2025)
This brief text is a dialogue with my ongoing research. It is not a summary, nor is it intended to be an excerpt, but rather a discussion on gender discourse in museums, with domestic labor as its central element. The main focus of this article is the exhibition The Daily Life of Women in Other Times, by artist João Maria Ferraz Diniz, inaugurated in 2015 at the Museu do Tropeiro – Seccional Casa de Sinhara, in Castro (PR). The exhibition portrays domestic labor as an intrinsic aspect of female knowledge rather than as a skill to be learned, performed, and valued. Through the analysis of selected images from the exhibition, I propose the observation and practice of the gaze as analytical tools for examining the constructed representations and historical narratives within the museum. Beyond materiality, I also consider the silent elements embedded in the pigments of the artworks, which enable a discussion on the devaluation of domestic labor, power relations, female norms, and class hierarchies. Although this research echoes masculine perspectives in theory, its primary approaches are rooted in feminine thought, taking into account women’s places of speech and the multiple roles they have undertaken and continue to perform in their personal and professional lives. This reflection aims to highlight the marginalization of domestic labor—an unpaid occupation treated as a natural part of family life, passed down to women across generations.Keywords: Gender; Museum; Museology; Casa de Sinhara; Domestic Craft.